CBDC as competitor for bank deposits and cryptocurrencies - Max Fuchs (Philipps-University Marburg, School of Business and Economics, 2022)
Private cryptocurrencies allow for payments without the need for a financial institution. These institutions, the central bank and retail banks, may thus observe a decline in the demand for their payments systems, i.e. cash and deposits. Using the monetary search model of Lagos and Wright (2005), we show that the central bank is able to tilt the playing field until it wins. By introducing an interest-bearing central bank digital currency (CBDC), the central bank is able to provide a payment system which is superior to cryptocurrencies. Miners cannot match the CBDC rate and go bankrupt. Retail banks, on the other hand, face lower profits but survive in the equilibrium. In addition, it can be welfare-improving to kick out cryptocurrencies by an interest-bearing CBDC.
Keywords: E41; E42; E51; E52; E58; 330; CBDC; cryptocurrencies; welfare analysis